KEHIDUPAN PETANI PADI DI KELURAHAN TUMOBUI KECAMATAN KOTAMOBAGU KOTA KOTAMOBAGU - Rondonuwu, Claudia Olvi (HOLISTIK, Journal Of Social and Culture, 2017)
Indonesia to the mainland a very broad and supported by geographical roadsstructure, tropics and is well suited to the cultivation of various agriculturalcommodities. Besides most of the people live in rural areas and his life is highlydependent on agriculture. Indonesia also having human resources quitedifferent. Social values the foundations for mutual cooperation or help oneanother the most important part in society. This is what makes life workedtogether to easier interwoven in Tumobui society, because can help andmutual assistance until all intractable.The Tumobui farmers in general tenant rice fields. They are not only comefrom the surrounding neighborhood but there are also farmers originatingoutside and mutually supported for efforts to improve the income to wellbeing. Therefore the farmers especially in urban Tumobui village understandon efforts to manage rice fields in the system mutual help. Human life as asociety to build and develop a habit or ability and customs held by the orgroup farmers.In the process of culture change especially at the Tumobui happened shiftcultural values. This influenced by the buildings (shop-houses and hospitality),resulting in agricultural land dwindling. This reality shows changes, in factsome forms of a system mutual cooperation that collapsed culture ordisappeared from a society.Keywords: farmers, mutual cooperation, rice